Analisis Spasial Penetapan Wilayah Pertambangan Rakyat (WPR) Bahan Galian Sirtu di Sungai Kampar Kecamatan Tambang dan Kecamatan Siak Hulu, Kabupaten Kampar, Provinsi Riau - , ZAKI HELMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The determination of small-scale mining area (WPR) is expected to be determined through the same stages as Mining Area (WUP). This then requires a proper analysis based on specific criteria suited for small-scale mining area as an important first step, as explained by the Law of RI No. 4 of 2009 on Mineral and Coal Mining. Spatial analyses, as a method, seeks to assist planners in analyzing the condition of the problem based on targeted regionâs data. There are three factors that support the research objectives, (1) geological, (2) surrounding environment, and (3) economic factor. Geological factors are used to assess the suitability of the proposed fluviatil sand and stone (sirtu) depositâs. The surrounding environment factorâs assess the WPRâs safe distance from residential areas, public facilities and infrastructure. The economic factor, on the other hand, assesses the recommendation for WPR development based on the distance between deposit and the site for loading and unloading minerals. WPRâs regional planning is done with Boolean logic spatial analysis and regional analysis methods. This procedure produces recommendation map for a WPR development. It is found in the research area there area 39 whose gravel and sand (Sirtu) deposits meet the WPRâs criteria. From a total of 39 locations, 14 of them are assigned as the priority I area. These 14 areas are scattered within 2 districts, in witch 5 areas are in The Tambang District, and the rest 9 areas are in The Siak Hulu District. Priority II are consist of 18 locations, in which 7 of them are located in The Tambang District, while the rest 11 are located in Siak Hulu District. Finally Priority III areas consist of 7 locations, in which 3 location are located in The Tambang District and 4 in Siak Hulu District.